Removal of Nickel from Aqueous Solution using Coconut Fiber Char as Low Cost Adsorbent - Krishnan Moorthy, Vivendran (Universiti Teknologi PETRONAS, 2016)
The project focal emphasis is to synthesis and characterization a coconut fiber char (CFC) as low cost adsorbent for removal of nickel. Coconut fiber was selected as a based precursor for the char adsorbent. The synthesis was carried out by carbonization treatment. The treatment was done in different environment condition at temperature of 700oC. Coconut fiber char (CFC) was characterized to observe its morphology in scanning electron microscope (SEM), Fourier Transform Infrared (FTIR), Nitrogen adsorption/desorption analysis and CHNS/O analyser. The nickel adsorption evaluation will be carried out through a batch adsorption process. CFC-CCN were observed to have lower surface area and higher pore diameter compared to CFC-CFN. Moreover, the morphology of all three adsorbents demonstrated a wide range of molecule sizes with rough surfaces. The results show that CFC-CCA, CFC-CFN and CFC-CCN has a BET surface area in the range of 430-540 m2 /g and all of the adsorbents displays good efficiency in nickel ion adsorption (Qe=10.95 mg/g). Carbonized coconut fiber has gave a significant enhancement of Ni (II) adsorption capacity.